Theological diversity and canonical authority: an examination of how diverse viewpoints in the Old Testament may be acknowledged, interrelated, and allowed to function theologically - Goldingay, John (1983)
The OT manifests considerable theological diversity. But if it is in some sense 'one' book, its diverse viewpoints should be capable of being brought into a coherent mutual relationship.